2022
DOI: 10.3390/su14159125
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perceived Organizational Support and Employee Care on Turnover Intention and Work Engagement: A Mediated Moderation Model Using Age in the Post Pandemic Period

Abstract: The purpose of this study was to adopt the well-established and mature job demands–resources model (JD-R), and to extend its model to work engagement and turnover intention of frontline healthcare personnel. Using the cross-sectional survey and partial least squares path modeling tools, the results showed that perceived organizational support had a negative impact on the turnover intention of frontline healthcare staff. This finding is important because it shows how the medical system managers can buffer the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 89 publications
(144 reference statements)
0
6
0
Order By: Relevance
“…A cross-sectional survey has been conducted for front-line healthcare staff in China by Li, Mohamed [30] to measure the impact of organisational support on employee turnover intention. This study's results could verify that organisational support negatively affected employee turnover intention.…”
Section: Management Supportmentioning
confidence: 99%
“…A cross-sectional survey has been conducted for front-line healthcare staff in China by Li, Mohamed [30] to measure the impact of organisational support on employee turnover intention. This study's results could verify that organisational support negatively affected employee turnover intention.…”
Section: Management Supportmentioning
confidence: 99%
“…The objective of this research is to investigate the indirect relationship between employees' perceptions of organizational support and turnover intention. Relationship also shown to have direct effects in a study by Li et al(2022). Adopting the well-established and mature job demands-resources model (JD-R), they conducted a cross-sectional study by which they found that perceived organizational support had a negative impact on the turnover intention of frontline healthcare staff.…”
Section: Perceived Organizational Supportmentioning
confidence: 99%
“…The treatment will be responded according to what is received. Organizational support which includes the support of co-workers and supervisors considers welfare and values individual contributions to the organization (Li et al, 2022).…”
Section: Introductionmentioning
confidence: 99%